DIAGNOSIS OF THE USE OF ELECTRIC ENERGY IN SLAUGHTERHOUSE FOR POULTRY CHICKEN - Bueno, Leda; Rossi, Luiz Antonio; Souza, Sílvia Regina Lucas de; Teruel, Bárbara J.; Bueno, Benedito de Freitas (ENERGIA NA AGRICULTURA, 2015)
In slaughterhouses, the operations that occur are heavily dependent on electricity. This study aimed to diagnose, analyze and propose solutions that lead to the rational use of electricity, without interfering, or maintain, the quality of the final product on the production lines of a broiler slaughterhouse. The work was carried through in a slaughterhouse of broilers, located in São Paulo, in the period of 2004 to 2008. It was found that the compressors responsible for maintaining cold the refrigerated environment showed the highest consumption of electricity in the fridge, representing 97% of total consumption. It was observed that in none of the evaluated electric motors the power factor reaches the value recommended by ANEEL, and that possibly the energy efficiency indicators can be optimized. It was concluded that there are failures in electric energy use, demonstrating the need to implement an action plan that aims the conservation and rational use of energy and consequent reduction in production cost of chicken meat. Keywords: Electrical Energy Consumption, Indicators, Rational Use, Slaughterhouse. DIAGNOSIS OF THE USE OF ELECTRIC ENERGY IN A CHICKEN SLAUGHTERHOUSE RESUMO: Nos matadouros, as operações que ocorrem são altamente dependentes da eletricidade. Este estudo teve como objetivo diagnosticar, analisar e propor soluções que levem ao uso racional de energia elétrica, sem interferir, e manter, a qualidade do produto final nas linhas de produção de frangos de corte matadouro. O trabalho foi realizado em um matadouro de frangos de corte, localizada em São Paulo, no período de 2004 a 2008. Verificou-se que os compressores responsáveis pela manutenção da frio do ambiente refrigerado apresentaram o maior consumo de electricidade no frigorífico, o que representa 97% do consumo total. Foi observado que em nenhum dos motores elétricos avaliados o fator de potência atinge o valor recomendado pela ANEEL, e que, possivelmente, os indicadores de eficiência energética pode ser otimizado. Concluiu-se que existem falhas no uso da energia elétrica, demonstrando a necessidade de implementar um plano de ação que visa a conservação e uso racional de energia e conseqüente redução do custo de produção de carne de frango. Palavras-chave: Consumo de Energia Elétrica, Indicadores, Uso Racional, Matadouro.